Enantioselective synthesis of (R)-(+)-alpha-lipoic acid via proline-catalyzed sequential alpha-aminoxylation and HWE olefination of aldehyde - Panchgalle, Sharad P.; Jogdand, Ganesh F.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
An efficient enantioselective synthesis of (R)-(+)-alpha-lipoic acid is described, in high optical purity (>97% ee), using L-proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde as the key step. (C) 2010 Elsevier Ltd. All rights reserved.